Brand Trust dalam Konteks Loyalitas Merek: Peran Karakteristik Merek, Krakteristik Perusahaan, dan Karakteristik Hubungan Pelanggan-Merek - Rully Arlan Tjahyadi (Jurnal Manajemen Maranatha, 2006)
Brand loyalty or customer loyalty is an important concept for many company, it can brings many benefits for the company, such as repeat purchase and recommendation of the brands to others, and then can reduce marketing costs. The existing literature of brand loyalty has been focused on the roles of customer satisfaction guiding their subsequent actions. In this context, the shifting emphasis to relational marketing has devoted a lot of effort to analyze how other constructs such as brand trust predict future intentions. Trust in a brand is important and is a main factor in the development of brand loyalty. Factors that can influence trust in a brand include a number of brand characteristics, company characteristics, and consumer-brand characteristics. Marketers should, therefore, take consideration of brand factors in the development of trust in a brand. The focus of this paper is to discuss factors affecting the development of trust in a brands, and to represent how that trust affect to brand loyalty.